Analisis Politik Luar Negeri Rusia dalam Penangguhan Ratifikasi Uji Coba Nuklir sebagai Dewan Keamanan Tetap PBB - Cahyaningrum, Karin Wahyu; Oktasafea, Aura Putri; Sha'diah, Fadhila Nur (Journal of Integrative International Relations, 2025)
Nuclear is a big threat to world countries. The new foreign policy issued by Russia is related to the suspension of ratification of the Comprehensive Nuclear Test Ban Treaty (CTBT). To be precise, on October 05 2023, the Russian Parliament agreed to announce that Russia withdrew its ratification of the CTBT agreement. This action poses a new threat in the heat of the Russian-Ukrainian conflict. The results of this research explain the background that underlies Russia's decision to take a policy to cancel the ratification of the CTBT. Corresponding with the response of the United States in interpreting this Russian policy.